Assessment of Genetic Variability for Agro-Morphological Important Traits in Aman Rice (Oryza Sativa L.) - Sarwar, Golam; Hossain, Md. Sarowar; Rashid, Md.Harun -Ur-; Parveen, Shahanaz (International Journal of Applied Sciences and Biotechnology, 2015)
The present study was conducted in the experimental farm, Sher-e-Bangla Agricultural University (SAU), Dhaka during July 2013-December2013. The analysis of variance revealed significant deviation for all the characters studied and indicated the existence of variation among thegenotypes. The PCV values were slightly higher than the respective GCV values for all the characters except unfilled grains per panicleindicating that the characters were less influenced by the environment. Total tillers per plant, effective tillers per plant, filled grains per panicle,unfilled grains per panicle and yield per plant showed high heritability coupled with high genetic advance percentage of mean which indicatedthe preponderance of additive gene action and such characters could be improved through selection. High heritability along with low geneticadvance as percentage of mean was found for plant height, days to 50% flowering, panicle length, days to maturity and thousand grains weightwhich indicated the non additive gene action for expression of these characters. Considering the genetic parameters and other agronomicperformances, the genotypes Special from AL-29, AL-36, PP-4B(i), AL-17(iii)B, AL-17(iii), AL-17(ii)A, Special from-129, Special from17(iv), AL-44(i), AL-17, Special from AL-36(D), PP-48, IR-25B, Special from AL-33, IR-25B (Tall), P-5B (ii) might be considered betterparents for future hybridization programme. DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.11896 Int J Appl Sci Biotechnol, Vol. 3(1): 73-79